Use of resource management systems (erp, bim) in industrial construction - IVANYNA, Oleksandr (Ways to Improve Construction Efficiency, 2025)
The integration of Enterprise Resource Planning (ERP) and Building Information Modeling (BIM) systems in industrial construction forms a new management paradigm focused on digital synchronization, transparency, and improving efficiency across all stages of a facility’s life cycle. The development of these technologies makes it possible to unite financial, material, temporal, and geometric data within a single information environment that ensures end-to-end resource management – from planning to operation. ERP systems provide centralized control of resource, financial, logistics, and personnel flows, while BIM focuses on visual and analytical modeling of the facility. Their integration creates an intelligent management platform capable of responding to changes in real time. The core idea lies in the creation of a Common Data Environment (CDE), where information is synchronized among all project participants, minimizing the risk of data duplication or loss. ERP systems gain direct access to BIM model parameters, allowing for the automatic updating of cost estimates, delivery schedules, work volumes, and equipment utilization levels. Through the use of API connections, IFC and COBie formats, and cloud-based platforms such as Autodesk Forge or Trimble Connect, an integrated interaction between systems is achieved. Such solutions enable simulated forecasting, model-based execution (MBE), and the creation of a Digital Twin of the facility. In industrial construction, ERP and BIM function not only as technical tools but also as strategic mechanisms for enhancing efficiency – reducing cost overruns, optimizing logistics, shortening implementation timelines, and controlling risks. Mathematical models describing ERP+BIM interactions, including analytical efficiency functions and digital deviation risk vectors, make it possible to quantitatively assess the results of digital integration. Efficiency is treated as an integral function dependent on the level of digital maturity, the speed of data updates, and the system’s scenario adaptability. Thus, the use of ERP and BIM in industrial construction provides the foundation for establishing a digital management ecosystem in which decisions are based on reliable data, and processes are monitored in real time. This approach improves planning accuracy, enhances project resilience, and strengthens the competitiveness of the construction industry.